Combination of Compound Kushen injection with first-line treatment versus first-line treatment alone for advanced colorectal cancer: a study protocol for a multicenter, openlabel, randomized controlled trial - Jingyuan Wu; Yuansha Ge; Guanghui Zhu; Ruike Gao; Xiaoyu Zhu; Ying Zhang; Jie Li (BMC Complementary Medicine and Therapies)
Abstract Background The treatment of advanced colorectal cancer (CRC) has progressed slowly, with chemotherapy combined with targeted therapy being the first-line treatment for the disease, but the improvement in efficacy is not satisfactory. Compound Kushen injection (CKI) is one of the representative drugs of anti-cancer Chinese herbal injection drugs, which has been widely used in the adjunct treatment of cancer in China. The aim of this trial is to evaluate the efficacy and safety of CKI combined with first-line treatment of advanced CRC. Methods This is a multicenter, randomized, open-label controlled clinical trial in which 320 patients with advanced CRC will be randomly assigned to the treatment group or the control group in a 1:1 ratio. Both groups will receive at least 4 cycles of first-line therapy (FOLFOX/FOLFIRI/CAPEOX ± cetuximab/bevacizumab) in 14–21 day cycles, and the experimental group will receive additional CKI with a cumulative dose of 200 ml per cycle. Patients who achieve a complete response, partial response, or stable disease after 4–6 months will receive maintenance therapy until disease progression or another endpoint event, such as toxicity or death, occurs.. Follow-up will occur every 3 months until death or loss to follow-up. The primary outcome of this study will be progression-free survival (PFS). Secondary outcomes will be overall survival (OS), 1-year OS rate, 1-year PFS rate, objective response rate,disease control rate, symptoms and quality of life evaluation. Safety outcomes will be incidence of adverse events. Discussion This study will be the first randomized controlled trial to investigate the efficacy and safety of CKI when combined with first-line treatment in the treatment of advanced CRC, with PFS as the primary outcome. It aims to clarify the clinical advantages and therapeutic effect of CKI in the treatment of advanced CRC. To identify the benefit population of CKI in the treatment of patients with advanced CRC, an enrichment design based on biomarkers will be utilized. Metabolomics and gut microbiota analysis will be conducted on biological samples to explore the metabolic and gut microbiota differences associated with the efficacy of CKI, guiding further research into its mechanism of action. Trial registration ClinicalTrials.govNCT05894694. Registered on 4 August 2023.